Urbanization and religion in ancient Central Mexico - Carballo, David M. (Oxford studies in the archaeology of ancient states, 2015)
This volume examines the ways in which urbanisation and religion intersected in pre-Columbian central Mexico. It provides a materially informed history of religion and an archaeology of cities that considers religion as a generative force in societal change.